(3Mbhb GdChdhjI GdfGTFI Yf bjO GdMbhb GdeVehfI ai SLd GdVeGfGJ GdefbhdI (B/ s - (3JjehQ eMeO GdHcQi CMeOs; (3SejMI eUWai GdbdjhHis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3JQLY CgejI ehVhY GdQSGdI Edi chfg jJUd HacQI GdVeGfGJ GdefbhdI(B: (3h GdSLd GdPi JbjO ajg GdMbhb GdeVehfI GdhGQOI Ydi GdefbhdGJ(B. (3h acQI SLd GdVeGfGJ GdefbhdI SHbJfG EdjgG cKjQ ef GdJTQjYGJ GdZQHjI eKd GdJTQjY GdGSJQGdi h GdJTQjY GdfjhRdGfOi hGdeGOI (B9 (3ef GdbGfhf GdJLGQi GdehMO ddhdGjGJ GdeJMOI GdCeQjcjI h GdJTQjY GdaQfSi(B: (3h Ydi eSJhi GdTQb GdChSW cGf GdJTQjY GdeUQj (B115 (3dSfI (B2015 (3gh Chd JTQjY YQHj jbff ehVhY GdVeGfGJ GdefbhdI(B. (3h hLhO SLd YGe JbjO ajg cGaI CfhGY GdMbhb GdeVehfI GdhGQOI Ydi GdefbhdGJ (B((3ShGA Qghf(B: (3Ch Mbhb GeJjGR(B: (3Ch Mbhb bVGFjI(B...(3GdN(B): (3djS eYfGg GdJNdj Yf GdhSGFd GdJbdjOjI dQgf GdefbhdGJ(B: (3aGdQgf GdMjGRi ddefbhd h GJaGb GdSjWQI Ydi GdhOGFY GdHfcjI GdVGefI h WQb Qgf GdYdGeGJ GdJLGQjI h ZjQ Pdc ef GdQghf GdJbdjOjI dG jRGdhG bGFejf ai Xd hLhO SLd GdVeGfGJ GdefbhdI(B. (3dPdc cGf ef GdefWbj Cf jYed fXGe SLd GdVeGfGJ GdefbhdI HGdGJSGb eY SHd GdQghf GdJbdjOjI ddefbhd(B: (3h gPG eG YcaJ Ydjg dLfI GdCee GdeJMOI ddbGfhf GdJLGQj GdOhdi(B: (3HOkAG ef GdOdjd GdJTQjYi GdYGe ddVeGfGJ GdefbhdI (B2007 (3h GfJgGkAG HeTQhY GdbGfhf GdfehPLi ddVeGfGJ GdefbhdI (B1016s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2020s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B267-273s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdMbhb GdeVehfIs; (3GdVeGfGJ GdefbhdIs; (3Mbhb GeJjGRs; (3GdYdGeGJ GdJLGQjIs; (3aV GdJfGaSs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs